Evaluation of highly accelerated real‐time cardiac cine MRI in tachycardia. (21st November 2013) - Bassett, Elwin C.; Kholmovski, Eugene G.; Wilson, Brent D.; DiBella, Edward V. R.; Dosdall, Derek J.; Ranjan, Ravi; McGann, Christopher J.; Kim, Daniel
<x xml:space="preserve">Abstract</x> Electrocardiogram (ECG)‐gated breath‐hold cine MRI is considered to be the gold standard test for the assessment of cardiac function. However, it may fail in patients with arrhythmia, impaired breath‐hold capacity and poor ECG gating. Although ungated real‐time cine MRI may mitigate these problems, commercially available real‐time cine MRI pulse sequences using parallel imaging typically yield relatively poor spatiotemporal resolution because of their low image acquisition efficiency. As an extension of our previous work, the purpose of this study was to evaluate the diagnostic quality and accuracy of eight‐fold‐accelerated real‐time cine MRI with compressed sensing (CS) for the quantification of cardiac function in tachycardia, where it is challenging for real‐time cine MRI to provide sufficient spatiotemporal resolution. We evaluated the performances of eight‐fold‐accelerated cine MRI with CS, three‐fold‐accelerated real‐time cine MRI with temporal generalized autocalibrating partially parallel acquisitions (TGRAPPA) and ECG‐gated breath‐hold cine MRI in 21 large animals with tachycardia (mean heart rate, 104 beats per minute) at 3T. For each cine MRI method, two expert readers evaluated the diagnostic quality in four categories (image quality, temporal fidelity of wall motion, artifacts and apparent noise) using a Likert scale (1–5, worst to best). One reader evaluated the left ventricular functional parameters. The diagnostic quality scores were significantly different between the three cine pulse sequences, except for the artifact level between CS and TGRAPPA real‐time cine MRI. Both ECG‐gated breath‐hold cine MRI and eight‐fold accelerated real‐time cine MRI yielded all four scores of ≥ 3.0 (acceptable), whereas three‐fold‐accelerated real‐time cine MRI yielded all scores below 3.0, except for artifact (3.0). The left ventricular ejection fraction (LVEF) measurements agreed better between ECG‐gated cine MRI and eight‐fold‐accelerated real‐time cine MRI (mean difference, –1.6%) than between ECG‐gated cine MRI and three‐fold‐accelerated real‐time cine MRI (mean difference, –5.7%). Eight‐fold‐accelerated real‐time cine MRI with CS yields acceptable diagnostic quality and relatively accurate LVEF measurements in the challenging setting of tachycardia. Copyright © 2013 John Wiley & Sons, Ltd.